Towards accident-free construction sites: The role of human resource management – A review - N Munu; PA Owusu; R Kizza; AAhumuza; N Banadda; I Kabenge (African Journal of Environmental Economics and Management, 2017)
Rural-urban migration has put a lot of pressure on governments and private sector actors to provide decent infrastructurehousing in many developing parts of the world. Buildings for example, are hastily put up to meet ever growing demand for housing and in so doing raise the risk of accidents at construction sites. The occurrence and widely publicized construction site accidents has attracted a lot of international and local concern. Although the challenges are multi-faceted, the role of Human Resource Management (HRM) play a pivotal role in this dynamic industry. As such, the aim of this paper is to review construction accidents with a bias towards better HRM to reduce them in the industry. It can be concluded that proactive HRM in the form of Tier II Workforce Management Strategy significantly solves the construction site accident problems.